2006
DOI: 10.1080/13607860600641200
|View full text |Cite
|
Sign up to set email alerts
|

Age, gender, and the underutilization of mental health services: The influence of help-seeking attitudes

Abstract: The objectives of this study were to explore age and gender differences in attitudes toward seeking professional psychological help, and to examine whether attitudes negatively influence intentions to seek help among older adults and men, whose mental health needs are underserved. To achieve these objectives 206 community-dwelling adults completed questionnaires measuring help-seeking attitudes, psychiatric symptomatology, prior help-seeking, and intentions to seek help. Older age and female gender were associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

71
511
19
16

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 722 publications
(617 citation statements)
references
References 37 publications
71
511
19
16
Order By: Relevance
“…The help-seeking propensity scale refers to an individuals’ intention and ability to seek help. Similarly, Mackenzie et al (2006) found a strong predictive association between help-seeking propensity and intentions to seek professional help. Intentions in turn were described as the strongest predictor for actual help-seeking behaviour (Ajzen, 1985).…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…The help-seeking propensity scale refers to an individuals’ intention and ability to seek help. Similarly, Mackenzie et al (2006) found a strong predictive association between help-seeking propensity and intentions to seek professional help. Intentions in turn were described as the strongest predictor for actual help-seeking behaviour (Ajzen, 1985).…”
Section: Discussionmentioning
confidence: 87%
“…Mackenzie, Gekoski, & Knox, 2006; ten Have et al, 2010) and being Caucasian (Ward, Wiltshire, Detry, & Brown, 2013) was correlated with more favourable attitudes. Young adults were reported to have less positive attitudes towards seeking professional help than older adults (Gonzalez, Alegria, & Prihoda, 2005; Robb, Haley, Becker, Polivka, & Chwa, 2003).…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations